Productivity and Profitability of Abaca Varieties/Hybrids (Musa textiles Nee) Under Mature Tall Coconuts in Davao City, Southern Mindanao, Philippines - Secretaria, M. I.; Eroy, M. N.; Macarayan, O. B. (International Coconut Community Journal, 2012)
Two abaca varieties; Tangongon and Maguindanao, and two hybrids; Magino and Bongtang were grown under mature Laguna Tall coconuts spaced 9x9 m triangular in Bago Oshiro, Davao City from 2006-2010. The growth, yield and economic performance of these varieties/hybrids were evaluated to identify varieties/hybrids suitable as coconut intercrop and to show its suitability as coconut+abaca intercropping. Magino, a cross between Maguindanao and Inosa, was the consistent highest yielder. It had good yield attributes like good suckering ability, taller and bigger plants contributing to high fiber yields and high economic returns i.e. NPV and BCR. Maguindanao variety and Bongtang hybrid had comparable performance with Magino hybrid. Tangongon variety is the consistent lowest yielder with yield and yield attributes inferior to the rest of the plants tested affecting its profitability. Crop Fertilizer Use Efficiency (CFE) using fiber yield as an index revealed that top yielding entries are more efficient in converting fertilizer inputs into economic yield as reflected by their high CFEs. Abaca is a highly suitable intercrop for coconut and coconut areas could be used as expansion areas for growing the crop. Profitability of abaca farming under coconut is influenced by the variety used. Some drawbacks in abaca farming and good practices are discussed.